Cobalt based catalysts for CO Preferential Oxidation - Gómez, Leticia Ester (2019)
In this work, catalysts based oncobalt supported on ZrO2 and CeO2, and CoCeMnOx were studiedfor the CO preferential oxidation (COPrOx) in rich-hydrogen stream able to feedfuel cells. Among them, the CoCeMnOx formulation showed the highest COconversion at low temperatures, while the cobalt oxide supported on ceriapresented the best selectivity toward CO2.The Co3O4 spinel was theactive phase for the CO Preferential Oxidation detected in all catalysts.However, the CoOx-CeO2 and CoCeMnOx catalysts resulted more activethan cobalt oxide supported on zirconia. The presence of ceria close to cobaltspecies promote the redox properties and enhance the catalytic activity. In theCoCeMnOx catalyst prepared by co-precipitation, the incorporation of Mnrepresented an additional positive effect. The presence of Mn promoted there-oxidation of Co2+ to Co3+ and, consequently, theactivity increased at low temperature. By XRD of CoOx-ZrO2 and theCoOx-CeO2 catalysts, the Co3O4 spinel and ZrO2or CeO2 were identified in agreement with Laser-Raman spectra.At the same time the CoCeMnOx catalyst, prepared by co-precipitation ofprecursor salts, showed an incipient development of a new phase (Mn,Co)3O4mixed spinel, due to the intimate contact between elements.